1992
DOI: 10.1177/0306312792022001009
|View full text |Cite
|
Sign up to set email alerts
|

Normative Reflexions on Constructivist Approaches to Science and Technology

Abstract: Systematic and fundamental thinking on normative, or normatively relevant, questions is virtually absent in the highly influential constructivist studies of science and technology. This paper is an attempt at changing this situation. After reviewing and assessing the role of normativity and reflexivity, in so far as it has been acknowledged within constructivism, a number of `normative reflexions' are presented. Three general approaches—social constructivism, ethnography and actor-network theory—are analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 11 publications
0
36
0
4
Order By: Relevance
“…In fact, a longstanding criticism of such 68 M. van Oudheusden approaches is that although they concern themselves with political and normative issues in science and technology, and despite their understanding that science is not a neutral, disinterested enterprise, they fail to critically engage with their own norms and politics (Radder 1992;Fuller 2000;Genus 2006;Pestre 2008). With a few notable exceptions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a longstanding criticism of such 68 M. van Oudheusden approaches is that although they concern themselves with political and normative issues in science and technology, and despite their understanding that science is not a neutral, disinterested enterprise, they fail to critically engage with their own norms and politics (Radder 1992;Fuller 2000;Genus 2006;Pestre 2008). With a few notable exceptions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Notes 7 This exploration is inspired by the work of Stengers (1997Stengers ( , 2000Stengers ( , 2003 whose work traces the ongoing 'invention' of the sciences and explains that the process of inventing science necessitates a productive tension between 'objectivity' and 'belief'. 8 Both Radder (1992) and Fraser (2006) raise cautions about the ethical overtones of Latour's approach to knowledge production. 9 Such is the aim of Latour (2005) and is discussed in Barry and Born (2013).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In these historical accounts the analysts remain agnostic about the knowledge claims and often implicit value judgements made by the diVerent relevant social actors (this is often referred to as methodological symmetry or as methodological relativism). 4 Indeed constructivist studies, based on methodological symmetry, are often criticized for not 'taking a stand' and getting caught up in a moral relativism (Winner 1993;Radder 1992). Wiebe Bijker, a prominent Wgure in the STS community, suggested that 'The STS agenda has been largely agnostic as to the normative and political issues related to the application of STS insights (Bijker 2003: 445).…”
Section: The Constructivist Ontologymentioning
confidence: 99%